Attenuation of cisplatin-induced acute kidney injury by sanguinarine: modulation of oxidative stress, inflammation, and cellular damage - Nur Elena Zaaba; Suhail Al-Salam; Sumaya Beegam; Ozaz Elzaki; Fatima Aldhaheri; Anas Nemmar; Badreldin H. Ali; Abderrahim Nemmar (Frontiers in Pharmacology)
IntroductionCisplatin (CP)-induced acute kidney injury (AKI) is a significant side effect of CP chemotherapy, driven by oxidative stress and inflammation. Sanguinarine (SANG), an alkaloid from the rhizomes of Sanguinaria canadensis and poppy-fumaria species, exhibits antioxidant and anti-inflammatory properties. This study examined SANG’s effect on CP-induced AKI in mice and its underlying mechanisms.MethodsMice were orally administered 5 mg/kg SANG for 10 days. On the seventh day, they received a single intraperitoneal CP injection (20 mg/kg) and were sacrificed on the 11th day.ResultsSANG significantly improved CP-induced decreases in body weight, water intake, urine volume, relative kidney weight, creatinine clearance, albumin-to-creatinine ratio, and plasma urea and creatinine levels. It also reduced elevated plasma neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, cystatin C, and adiponectin levels, as well as renal markers of inflammation and oxidative stress induced by CP administration. SANG normalized kidney mitochondrial dysfunction, DNA damage, and apoptosis caused by CP. It also inhibited the CP-induced increase in the expression of phosphorylated nuclear factor-κB and autophagy markers in the kidney. Histological analysis showed that SANG reduced acute tubular necrosis and intraluminal protein accumulation due to CP.DiscussionIn conclusion, SANG mitigated CP-induced AKI by reducing inflammation, oxidative stress, DNA damage, apoptosis, and autophagy. Pending more comprehensive pharmacological and toxicological assessments, SANG may be regarded as a potential therapeutic agent for mitigating CP-induced AKI.